Impact of Sociodemographic, Financial Experience, and Financial Socialization Agents to Financial Literacy among Adults in Jabodetabek - Andrea Yunike Hadi Poernomo; Bayu Wicaksono; Bistok Agustinus Situmorang; Cut Natya Rucitra; Florentina Laut; Lukas Setia Atmaja (Jurnal Manajemen Bisnis Digital Terkini, 2025)
This research aims to determine the impact of socio-demographic factors, financial experience, socialization agents, on financial literacy levels for adults in Jabodetabek. The population in this study was 300 respondents who were Jabodetabek residents aged 18 years and over who were collected via questionnaires from November to December 2022. Data analysis in this study used quantitative analysis with an analytical technique using purposive sampling. The results of this research found that the financial literacy level of Jabodetabek residents was not influenced significantly by gender, age, and family socialization agent, but was influenced significantly by education, income, experience, peers, and media financial socialization agent. Our findings indicate that individuals with higher financial literacy scores are more likely to save and hold stocks and bonds.